2010
DOI: 10.1089/pop.2008.0048
|View full text |Cite
|
Sign up to set email alerts
|

Is Pharmacologic Care of Chronic Obstructive Pulmonary Disease Consistent with the Guidelines?

Abstract: Chronic obstructive pulmonary disease (COPD) is a common chronic illness that affects an estimated 210 million people worldwide, including 12 million people in the United States. National and international guidelines for treatment of COPD recommend use of certain medications, especially bronchodilators and corticosteroids, but the extent to which these are used appropriately is largely unknown. The objective of this study was to determine the extent to which pharmacotherapy for COPD is consistent with guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Similar high prescription rates of ICS/LABA in COPD patients have been found in previous studies [5,6] and lower rates in others [12,13]. Although the use of ICS/LABA is recommended in subgroups of COPD patients, to our knowledge, no one has described the characteristics of patients who are prescribed this combination by their GP in real clinical practice.…”
Section: Discussionsupporting
confidence: 81%
“…Similar high prescription rates of ICS/LABA in COPD patients have been found in previous studies [5,6] and lower rates in others [12,13]. Although the use of ICS/LABA is recommended in subgroups of COPD patients, to our knowledge, no one has described the characteristics of patients who are prescribed this combination by their GP in real clinical practice.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies evaluating drug therapy rates in the COPD population have included use of SABAs across all severity levels, precluding a comparison with our study [12,13]. However, a recent study by Fitch et al evaluated drug therapy patterns by severity levels using a claims-based algorithm, and found that 26% of patients with moderate COPD in a commercially insured population were prescribed a long-acting bronchodilator [8].…”
Section: Discussionmentioning
confidence: 99%
“…At least half of all COPD patients do not receive recommended pharmacologic therapies [35], and many never see a pulmonologist. Even with correct pharmacologic therapies, inappropriate use of medications still poses a barrier to COPD care.…”
Section: Introductionmentioning
confidence: 99%